Usability Analysis Aplikasi Mobile Augmented Reality (MAR) untuk Multimedia Pembelajaran Motherboard (Aplikasi AR-Mobo) - Yoiceta Vanda; Dwiyanto Dwiyanto (P3M Politeknik Negeri Cilacap, 2023)
Currently, Augmented Reality (AR) technology has developed into an easy-to-use, efficient and effective technology for providing innovative educational media. Mobile Augmented Reality (MAR) is an Augmented Reality technology that utilizes mobile devices, for example, smartphones. The MAR application for multimedia learning on the motherboard is seldom used in classroom learning so the effectiveness of learning is less than optimal. The research objective was to determine the level of usability of the MAR application system using the USE questionnaire. According to Arnold M. Lund, Usability analysis has 4 aspects: usefulness, ease of use, ease of learning, and satisfaction. The method used is usability testing with 90 engineering students participating as research subjects. This study uses a questionnaire as a data collection tool and uses descriptive statistical analysis. The results of this study, that the average usability analysis score is 86.22 is included in the very feasible category, based on the system feasibility category table. The developed MAR application shows that it has provided better user interaction. This research has the benefit of knowing the use of MAR applications on students, for specific purposes, namely effectiveness, efficiency, and satisfaction. Lack of user motivation, and lack of features, will cause stress. This occurs when the system cannot meet the goals of its users.